2015
DOI: 10.1515/pjs-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

The “biological chamber” method – use of autologous platelet-rich plasma (PRP) in the treatment of poorly healing lower-leg ulcers of venous origin

Abstract: The presented method seems technically simple, effective and relatively inexpensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…All patients in this study showed complete resolution of these ulcers over 4-10 weeks after receiving adjunctive PRP therapy. 84 Another retrospective study examined 39 patients with chronic lower extremity wounds to evaluate the effectiveness of standard protocols combined with PRP gel. 85 This study demonstrated that the addition of PRP gel promoted wound healing after an average of 145 days in 83% of the wounds and decreased the amputation rate.…”
Section: Treatment For Chronic Ulcersmentioning
confidence: 99%
“…All patients in this study showed complete resolution of these ulcers over 4-10 weeks after receiving adjunctive PRP therapy. 84 Another retrospective study examined 39 patients with chronic lower extremity wounds to evaluate the effectiveness of standard protocols combined with PRP gel. 85 This study demonstrated that the addition of PRP gel promoted wound healing after an average of 145 days in 83% of the wounds and decreased the amputation rate.…”
Section: Treatment For Chronic Ulcersmentioning
confidence: 99%
“…Plasma is used in surgery, sports medicine and traumatology for the treatment of chronic wounds and in aesthetic medicine (12,13). Autologous platelet-rich plasma (PRP) is a source of many growth factors that play a key role in the process of normal wound healing, such as platelet-derived growth factor (PDGF), transforming growth factor-b (TGF-b) and vascular endothelial growth factor (VEGF) (13).…”
mentioning
confidence: 99%
“…Autologous platelet-rich plasma (PRP) is a source of many growth factors that play a key role in the process of normal wound healing, such as platelet-derived growth factor (PDGF), transforming growth factor-b (TGF-b) and vascular endothelial growth factor (VEGF) (13). In addition, the leukocytes present in the preparation increase its antibacterial properties (12). Having been administered plasma, patients may take fewer standard drugs, which is particularly important in the case of concurrent diseases.…”
mentioning
confidence: 99%
“…Prospective Cohort FT = 1 year Leucocyte-and platelet-rich fibrin (L-PRP) (n = 32) 2b/B Waniczeket al (21) 2015 Poland…”
Section: Resultsmentioning
confidence: 99%